2015
DOI: 10.2147/ndt.s87089
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine ameliorates changes in hippocampal energy metabolism in chronic mild stress-exposed rats

Abstract: The molecular mechanisms underlying stress-induced depression have not been fully outlined. Hence, the current study aimed at testing the link between behavioral changes in chronic mild stress (CMS) model and changes in hippocampal energy metabolism and the role of paroxetine (PAROX) in ameliorating these changes. Male Wistar rats were divided into three groups: vehicle control, CMS-exposed rats, and CMS-exposed rats receiving PAROX (10 mg/kg/day intraperitoneally). Sucrose preference, open-field, and forced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 91 publications
(105 reference statements)
1
0
0
Order By: Relevance
“…Interestingly, normalization of mRNA levels of members of the IL-6/JAK2/STAT3 pathway in the hypothalamus by administration of the SSRI paroxetine coincided with normalization of the depressive-like behaviors induced by CMS. Consistent with our results, a previous study found that paroxetine can reverse CMS-related depressive-like behavior, as seen in the FST and sucrose preference tests [62-64]. Previous studies revealed that paroxetine ameliorates depressive-like behaviors by improving brain inflammation and oxidative stress, reducing HPA axis hyperactivity, elevating BDNF (brain-derived neurotrophic factor) expression, and inhibiting serotonin and norepinephrine uptake [65-67].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, normalization of mRNA levels of members of the IL-6/JAK2/STAT3 pathway in the hypothalamus by administration of the SSRI paroxetine coincided with normalization of the depressive-like behaviors induced by CMS. Consistent with our results, a previous study found that paroxetine can reverse CMS-related depressive-like behavior, as seen in the FST and sucrose preference tests [62-64]. Previous studies revealed that paroxetine ameliorates depressive-like behaviors by improving brain inflammation and oxidative stress, reducing HPA axis hyperactivity, elevating BDNF (brain-derived neurotrophic factor) expression, and inhibiting serotonin and norepinephrine uptake [65-67].…”
Section: Discussionsupporting
confidence: 91%